(untitled) (Medical Forum Monthly, 2024)
Background: In this part of the world anemia is one of the major public health problems especially in pregnant women. In our country the most important cause of anemia is poor diet repeated pregnancies and lack of awareness about contraception. Anemia can easily be managed with well nourish diet, with supplements of iron folic acid and multivitamin tablets. In our areas socio-economic problem is one of the causes which can be cope with help of Government and Non- Governmental Organizations by providing iron tablets and iron fortified foods to the population as a prophylaxis. To improve their health, pregnant women should regularly visit the clinics of Obs & Gynae and follow instructions of attending doctors and practice birth spacing in between the pregnancies. Object: To determine the incidence of anemia in pregnant women in different socioeconomic classes in rural areas. Study Design: Cross-sectional observational study. Place and Duration of Study: This study was conducted at the Department of Gynae & Obs, Peoples Medical College Nawabshah, and Sindh Pakistan from 1st March 2009to 30th June 2009. Patients and Methods: 850 pregnant ladies were included in the study who came to attend the antenatal clinic; where their history and clinical examination were recorded on a Performa. The ladies were divided into three socioeconomic classes, the higher, middle and lower class. 3ml of blood sample was taken from all the ladies for hemoglobin estimation and other necessary Lab test Results: A total number of 850 participants were included in this study, out of those 329 pregnant women were having hemoglobin (Hb) below 9 gm/dl, declared as anemic, the incidence as observed was 38.77 % and the highest incidence was found in lower socioeconomic class. Conclusion: It can be concluded from this study that anemia is one of the major problem in pregnant women of rural areas. The incidence observed was 38.77% which was least (0.6%) in higher class and was highest (60.2%) in lower socioeconomic class.